Meningkatkan Prestasi Belajar Mata Pelajaran Al Qur’an Hadits dengan Metode Demonstrasi di Madrasah Ibtidaiyah Muhammadiyah Cekelan - Muhammad Komarun; Bisri, Moh (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This research aims to find out: 1). Increasing Learning Achievement in Al Qur'an Hadith Subjects in Learning Hadith About Taqwa Using the Demonstration Method 2). Factors that support and hinder the implementation of the Demonstration Method in Hadith Learning about Piety in the Al Qur'an Hadith Subject class IV Semester I at MI Muhammadiyah Cekelan for the 2022/2023 Academic Year. This research is a type of classroom action research using descriptive methods. The subjects in this research were teachers of the Al-Quran Hadith subject, and supporting informants namely students. The results of this research are as follows: (1). Preparation for the Application of the Demonstration Method in Learning Hadiths About Taqwa Subjects of the Qur'an Hadith For students, namely preparing learning materials, formulating goals to be achieved, preparing the tools or media needed, arranging the place and estimating the time that will be used in learning using demonstration method. (2). Supporting factors are adequate facilities, sufficient time for learning, enthusiasm from the children, and an interesting and non-monotonous learning process. Meanwhile, the inhibiting factors for implementing the Demonstration Method in Learning Hadith about Piety in the Qur'an Hadith Subject class IV Semester I at MI Muhamadiyah Cekelan are differences in students' ability levels, some children like to talk to themselves and play alone, children lack self-confidence